Intelligible History, Negated Subjects: The Pressures of Intimacy in Michael Crummey's and Michael Winter's Historical Novels - Hernáez Lerena, María Jesús (Miscelánea - Departamento de Filología Inglesa y Alemana, Universidad de Zaragoza, 2021)
This article explores the implications of Lauren Berlant’s essay “Trauma and Ineloquence” (2001) regarding the therapeutic effects of narrative, also addressing the critical work of other theorists that have tackled the question of the artificiality of personal and historical narratives. By connecting Berlant’s insights into the notion of intelligibility with those of Roland Barthes, of testimony theorists and of other critics on ineloquence, my analysis aims to throw light on two historical novels that are articulated through intimate events that prevent certain speakers (Berlant’s negated subjects) from producing testimony and, therefore, participating in mainstream narratives and accessing justice. The novels River Thieves (2001) by Michael Crummey and The Big Why (2004) by Michael Winter hold the past as a scandal where carnal entanglements degrade the epic sweep of the events and show the disruptive effects of non-normative knowledges. Intimacy, thus defined as a lawless and shameful element in society, intersects with the economic and sexual pressures imported into the colonies by the empire (Povinelli 2006; Stoler 2006a). In this context, Newfoundland, in Canada, represents a colony where the ethics of European and American civilization are called into question.